36+7n=-7+6(4n-7)

Simple and best practice solution for 36+7n=-7+6(4n-7) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 36+7n=-7+6(4n-7) equation:


Simplifying
36 + 7n = -7 + 6(4n + -7)

Reorder the terms:
36 + 7n = -7 + 6(-7 + 4n)
36 + 7n = -7 + (-7 * 6 + 4n * 6)
36 + 7n = -7 + (-42 + 24n)

Combine like terms: -7 + -42 = -49
36 + 7n = -49 + 24n

Solving
36 + 7n = -49 + 24n

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '-24n' to each side of the equation.
36 + 7n + -24n = -49 + 24n + -24n

Combine like terms: 7n + -24n = -17n
36 + -17n = -49 + 24n + -24n

Combine like terms: 24n + -24n = 0
36 + -17n = -49 + 0
36 + -17n = -49

Add '-36' to each side of the equation.
36 + -36 + -17n = -49 + -36

Combine like terms: 36 + -36 = 0
0 + -17n = -49 + -36
-17n = -49 + -36

Combine like terms: -49 + -36 = -85
-17n = -85

Divide each side by '-17'.
n = 5

Simplifying
n = 5

See similar equations:

| -5(-8x-3)+2=-19+4x | | -3+3x=4(x-3)+7 | | 3x+9+30=105 | | 4x-20x=24 | | 0.5x-1.5=-0.4x-3.6 | | (2×-3)/4=9 | | 30+2x+9+x=180 | | -1/7x=-9 | | 2(x+3)-3=88-3x | | -3+5(m-5)=-20+6m | | 0.5x-1.5=0.4x-3.6 | | y-9=-1/7x | | 103.5=9(m+3.9) | | 4-8x=3(-7x-3) | | 3x-251=1189 | | 75+33x+9=180 | | 16x-23=57 | | 2982=42(p+20) | | 105+105+x=180 | | 4xy+2b-(3xy)-5b= | | 3x+9+x+x=180 | | 3x+20=2x-40+2x+20 | | -3+8m=11-4-2m | | 15a+5b=255 | | 736=4(x+17) | | y+(-19)= | | 3x+9+30=180 | | 2(-7k-3)+9= | | 2-144x^2= | | 7x+3y+9=0 | | -13.00+2.00=11.00 | | -6(7+2m)-8m= |

Equations solver categories